WhatsApp-Assisted JCL-Based Physics E-Book: Its Effect on Physics Learning Outcome in Senior High School - Ivandra Immanuela Latumakulita; Supahar Supahar; Suparwoto Suparwoto; Ence Surahman (Postgraduate, University of Mataram, 2023)
This research aims to develop physics e-book-based jigsaw cooperative learning (JCL) assisted by WhatsApp. This article describes the results of the validity and effectiveness of the developed media on physics learning outcomes in terms of student learning motivation. This article also describes the relationship between initial ability and learning motivation on student learning outcomes. This research is development research with a 4-D model. This research was implemented with a quasi-experimental using a pretest-posttest control group research design. The sample in this research was 70 students of 10th grade science class at one of the high schools in Yogyakarta. The results of this research indicate that the development of WhatsApp-assisted JCL-based Physics e-book on the topic of straight motion is valid and reliable. This is evidenced by the results of the validator where the average value of validity and reliability is 0.75 in the high category and 94 in the reliable category. The use of WhatsApp-assisted JCL-based Physics e-book has a significant effect on improving student learning outcomes. This is indicated by the significant value is 0.00 < 0.05. By analysis of covariance, initial ability and learning motivation have a relationship with student learning outcomes. This is indicated by the squared value of the regression coefficient is 38.6%.